SISTEM INFORMASI GEOGRAFIS PEMETAAN WARGA NEGARA ASING - Reni Yunita; Samsudin Samsudin; Raissa Amanda Putri (LPPM Universitas Abdurrab, 2022)
Foreign Citizens are recorded in a government agency, namely the Class II Immigration Office of Tanjung Balai Asahan in the field of Immigration Intelligence and Enforcement. The information available at the Immigration Office is limited to data in the form of tables containing information from the foreigner, so that when the data increases, it will be difficult for officers to search for foreigner data. Therefore, we need a geographic information system regarding the distribution of foreigners. This research uses Leaflet, and Quantum GIS for map visualization. The existence of this geographic information system can provide information about foreigners to the public in order to socialize the presence of foreigners, and can also report the presence of foreigners who have not been registered, and can support immigration services for the supervision of foreigners.